Late surgical treatment of tetralogy of Fallot - Tchoumi, JCT (Clinics Cardive Publishing, 2011)
AIM: To study early post-operative results and follow up of patients over a year old, operated on for tetralogy of Fallot (ToF). METHODS: This retrospective analysis included 22 patients (14 male and eight female) with a mean age of 9.18 ± 6.5 years (range 13.5 months to 26 years), who underwent complete repair of ToF between April 2003 and June 2009. Data from patients’ records, pre-operative cardiac catheterisation studies, operative intervention, and pre-operative and postoperative two-dimensional echocardiographic studies were reviewed. All patients underwent complete repair including closure of ventricular septal defect (VSD). A trans-annular patch was used in 12 patients while an infundibular patch was used in 10 others. Patients were evaluated one, three, six and 12 months after surgery, and annually thereafter. The duration of follow up was from eight months to six years post surgery. RESULTS: Classical ToF was found in 10 patients. Twelve cases had associated anomalies: two patients with hypoplastic pulmonary artery branches, two with arterial duct malformations, and eight had proximal stenosis of the left branch of the pulmonary artery. NHYA class distribution was as follows: class I: two patients; class II: five subjects; class III: 10 patients; class IV: five subjects. The mean stay in hospital was 15 ± 7 days. Two patients (9%) died during the early post-surgical period. At a mean follow-up interval of 32 ± 9 months, all patients were asymptomatic and in NYHA class I. No late deaths occurred. In three patients, we registered isolated monomorphic ventricular extrasystoles. The right ventricle outflow tract (RVOT) pressure gradient was 29 ± 1.5 mmHg in the acute post-surgical period and it did not change significantly during follow up. The right ventricular function was defined as normal in 95% of the patients in the study and was mildly depressed in 5%. CONCLUSION: Even if treated later in life, our study showed very good surgical results of patients with ToF.